Odpowiedzi

Najlepsza Odpowiedź!
2009-11-28T17:38:02+01:00
A) n² + n

- dla n = 3
3² + 3 = 9 + 3 = 12
- dla n = 5
5² + 5 = 25 + 5 = 30
- dla n = 6
6² + 6 = 36 + 6 = 42

b) n³ - n

- dla n = 2
2³ - 2 = 8 - 2 = 6
6 : 6 = 1
- dla n = 6
6³ - 6 = 216 - 6 = 210
210 : 6 = 35

c) (2n + 1)²

- dla n = 2
(2 * 2 + 1)² = 5² = 25
- dla n = 5
(2 * 5 + 1)² = 11² = 121

d) (n + 1) - n²

- dla n = 2
(2 + 1) - 2² = 3 - 4 = -1
- dla n = 6
(6 + 1) - 6² = 7 - 36 = -29
2 1 2
2009-11-28T19:26:18+01:00
A) n² + n

- dla n = 3
3² + 3 = 9 + 3 = 12
- dla n = 5
5² + 5 = 25 + 5 = 30
- dla n = 6
6² + 6 = 36 + 6 = 42
2 1 2